1987
DOI: 10.1302/0301-620x.69b2.3818762
|View full text |Cite
|
Sign up to set email alerts
|

Vibration arthrography as a diagnostic aid in diseases of the knee. A preliminary report

Abstract: The detection and recording of vibration emission from human joints, a technique which we have termed "vibration arthrography", is a sensitive, non-invasive method for the objective study of the locomotor system. Using vibration sensors attached to bony prominences around the knee, we studied the joints of both normal and symptomatic subjects. Normal subjects produced three signal types-physiological patellofemoral crepitus, patellar clicks, and the lateral band signal. In symptomatic subjects we indentifled a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
4

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(58 citation statements)
references
References 0 publications
3
51
0
4
Order By: Relevance
“…Several causes of crepitus have been described [3][4] [5], but previous research has focused on the pathological meaning of crepitus. No research has demonstrated a definitive link between noise and pathology, and McCoy et al, (1987) [6] demonstrate that 99 percent of a cohort of subjects with no pain had patellofemoral crepitus. Overall its importance and meaning is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several causes of crepitus have been described [3][4] [5], but previous research has focused on the pathological meaning of crepitus. No research has demonstrated a definitive link between noise and pathology, and McCoy et al, (1987) [6] demonstrate that 99 percent of a cohort of subjects with no pain had patellofemoral crepitus. Overall its importance and meaning is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although therapies that might modify OA cartilage are still experimental or in development (25), reproducible means of assessing cartilage non-invasively would be useful in clinical tests of such agents. Small accelerometers (microphones) can record and quantitate crepitus, and could be used to enhance the precision of the examiner's hand (26). Whether investigators conducting field studies of OA might benefit from compartment-directed crepitus as assessment tools remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Some sounds are produced by patellofemoral crepitus (a fine crunching noise, usually on bending the knee from standing, which is said to be due the kneecap cartilage rubbing against the underlying cartilage of the femur) or when the plica (a thin wall of fibrous tissue that are extensions of the synovial capsule of the knee) snaps over the end of the femur (Beverland et al 1986;McCoy et al 1987). Other studies provide clear evidence that the anatomic source of the cracking sound associated with spinal high-velocity low-amplitude thrust manipulations is associated with cavitation of the synovial fluid (Watson and Mollan 1990;Evans 2002).…”
Section: Cavitation In Synovial Liquidmentioning
confidence: 99%